Improving Data Literacy in HEINEKEN (2023)
The following document is an undergraduate thesis on Improving Data Literacy in HEINEKEN. The paper includes a literature review, current situation analysis, desired situation, strategic options, recommendations, and an implementation plan. HEINEKEN is a global leader in the beer industry, with over 300 beer and cider brands across the world. Its Global Analytics Team is focused on data-driven decision-making, while its EverGreen strategy helps future-proof the business. To achieve sustainable growth, HEINEKEN aims to become data-driven and prioritize sustainability, responsibility, talent, and digital interactions. The Global Analytics team aims to develop data analytics and literacy across departments, evaluate their effectiveness, and improve data-driven decisions by implementing new initiatives and measuring progress. Global Analytics uses various communication channels and tools, including Speed Dates, Ambassadors calls, and SharePoint, to improve employees' data literacy and promote data-driven decision-making. KPIs are utilized to measure employee engagement and interest levels, and SharePoint offers a collaborative platform for employees to exchange information and best practices related to data analytics. HEINEKEN aims to improve its data literacy and decision-making levels and intends to identify the factors that influence decision-making and put improvements in place. HEINEKEN's Maturity Assessment Tool for Data Analytics helps measure the data analytics maturity of OpCos to identify areas for improvement and opportunities for growth. It focuses on personnel, process, and technology, and is a part of the Analytics Guru training program to advance a data-driven culture. Improving data-driven decision-making requires education and training in data literacy skills. HEINEKEN seeks to assess its data literacy level and customize a program to enhance its employees' skills and promote a data-driven culture. Effective communication is also crucial.